(untitled) (Perner’s Contacts, 2011)
Great companies whose number of retail and supplier units are numerous face complexities due to the large number of suppliers, large number of products and the scale of distribution. It’s essential for them to have supply chain well managed. Distribution is one of the key strengths. Right distribution set up is influencing landed cost of the goods for customer on high level. Nowadays when companies face high level of uncertainty it is not always clear that the cheapest solution is the best one. What other factors do we have to define the best solution?